Solitons in dual-core optical fibers with chromatic dispersion - Ozisik, Muslum; Bayram, Mustafa; Secer, Aydin; Cinar, Melih (SPRINGER, 2023)
In this paper, some analytical solutions for a model of dual-core optical fibers governed by a system of coupled non-linear Schrodinger equations (NLSEs) and the effect of the coefficient of the group velocity dispersion term on the considered model are investigated. The group velocity dispersion (GVD) has a important role in the optical wave propagation. The enhanced modified extended tanh expansion method (eMETEM) is successfully implemented to the governing model. The NLSE system is turned into a nonlinear ordinary differential equation (NLODE) via appropriate wave transformations. Supposing that the NLODE has solutions in the form suggested by the method and utilizing the enhanced solutions of the Riccati equation, we gain a nonlinear system of algebraic equations. The solutions of the governing model are obtained after solving the system of algebraic equations. 2D, 3D and contour illustrative figures for the physical interpretation of the attained solutions are presented. Besides, the result of the investigation, which is related to the effect of the coefficient of the group velocity dispersion term, is presented by supporting the various graphical scheme.
Keywords: Group velocity dispersion; Dual-core optical fibers; Soliton propagation; Modified extended tanh expansion method; Enhanced Riccati solutions; NUMERICAL-SOLUTION; EQUATION; POWER; LAW; NONLINEARITY; PERTURBATION; MODEL; DARK; Engineering; Physics; Optics